AN ANALYSIS OF TEACHERS’ AND PARENTS’ IT CAPABILITY IN ONLINE LEARNING IMPLEMENTATION - Darius Antoni; Suriani; Ardiansyah (PPPM Institut Teknologi Pagar Alam, 2023)
IT cabalility refers to ability to master information technology such as designing learningcontent, managing learning resources, building student learning independence, and communicating invarious directions. A good pattern of active interaction must be built, learning activities can be controlled,learning difficulties can be overcome, learning outcomes are guaranteed and quality, and can evaluatelearning. The first methodology used in this study is to conduct a literature study, namely by looking forprevious studies, related books that are relevant to the research conducted. The next stage is to identifythe problem to be studied, then design and collect data. Data was collected by distributing questionnairesto teachers and parents of public and private junior high school students in Talang Kelapa District,Banyuasin Regency. The discussion was carried out regarding data processing in general from researchthat has been carried out by researchers. Conclusions from the analysis of the ability of teachers andparents of junior high school students in Talang Kelapa District, Banyuasin Regency in using informationtechnology during the Covid-19 period showed that both have good ability to utilize technology mediaand applications to support online learning activities during the Covid-19 pandemic learning period.